The Sovereignty and Kinship Challenge: Addressing Indonesia-Timor Leste Border Security in the Post-Conflict Era - Nurisnaeny, Poppy Setiawati; Damayanti, Angel; Mubaroq, Sugeng Rifqi; Perdana, Ilham Azhar (Jurnal Ilmu Kepolisian, 2025)
Border security in post-conflict regions faces fundamental paradoxes between state sovereignty and socio-cultural realities. This study examines the Indonesia-Timor Leste border security in Belu Regency through the qualitative method using a case study design. The data were obtained from literature reviews, interviews with 11 key informants from security institutions, and secondary sources that are relevant to the study. Findings reveal three simultaneous border typologies—antecedent, subsequent, and superimposed boundaries—creating structural complexities beyond technical solutions. Kinship networks function as double-edged swords: they provide social capital for reconciliation, yet vulnerabilities are exploited for transnational crime when security policies overlook the social legitimacy of these networks. Institutional coordination remains reactive-informal, relying on personal relationships rather than systematic integration. The study extends Portes' social capital theory by demonstrating how state policies themselves transform social capital into security liabilities. Three practical recommendations emerge: reactivating biometric-based Border Crossing Permits with guaranteed accessibility, developing integrated Border Management Systems connecting six agencies, and institutionalizing community-based border management. Comparative lessons from Indonesia-Malaysia borders confirm that effective security requires balancing territorial sovereignty with legitimate community needs through formal coordination platforms and soft border approaches.